THE CAPABILITIES OF COMPUTED TOMOGRAPHY AND MAGNETIC RESONANCE IMAGING IN ASSESSING THE LOCAL INVASION OF LUNG CANCER - Mekhtiyeva, A.Y. (World of Medicine and Biology, 2022)
The purpose of the study was an assessment the diagnostic capabilities of computed tomography and magnetic resistance imaging in evaluating the local invasion of lung cancer. 320 patients with lung cancer who were hospitalized from 2010 to 2013, were observed. The mean age of the patients was 52.3±0.3 years (35 to 75 years). Computed tomography and magnetic resonance imaging were performed to detect cancer invasion. The specificity, sensitivity, and accuracy of the methods were calculated. The most reliable signs of cancerous invasion of the pleura were such as the presence of “tumor-pleural” paths, as well as thickening of the pleura at the border of contact with the tumor for more than 3 cm (r=0.787 and r=0.705, respectively). In determining the signs of cancerous invasion of the chest wall, CT demonstrated high sensitivity of 86.9 % and accuracy of 76.8 %, but low specificity (49.0 %). MRI was characterized by high sensitivity (75 %), accuracy (70 %), but low specificity (50 %). According to obtained results we can recommended both computed tomography and magnetic resistance imaging for detection of local cancer invasion.
Keywords: lung cancer; radiation diagnostic methods; pleural invasion; regional metastases